Histone Deacetylase Inhibition Protects Mice Against Lethal Postinfluenza Pneumococcal Infection. Issue 10 (October 2016) - Yagi, Kazuma; Ishii, Makoto; Namkoong, Ho; Fujii, Hideki; Asami, Takahiro; Suzuki, Shoji; Asakura, Takanori; Mizoguchi, Kosuke; Kamo, Tetsuro; Tasaka, Sadatomo; Iwata, Satoshi; Kunkel, Steven L.; et al.
Abstract : Objectives: Secondary bacterial pneumonia following influenza virus infection is associated with high mortality, but the mechanism is largely unknown. Epigenetic gene regulation appears to play key roles in innate and adaptive immunity. We hypothesized that histone acetylation, a major epigenetic mechanism associated with transcriptionally active chromatin, might contribute to the poor outcome of postinfluenza pneumonia. Design: Prospective experimental study. Setting: University research laboratory. Subjects: C57BL/6 male mice. Interventions: Mice were infected intranasally with 1.0 × 10 4 colony-forming units of Streptococcus pneumoniae, 7 days after intranasal inoculation with five plaque-forming units of influenza virus A/H1N1/PR8/34. The mice were intraperitoneally injected with the histone deacetylase inhibitor trichostatin A (1 mg/kg) or vehicle once a day from 1 hour after pneumococcal infection throughout the course of the experiment. The primary outcome was survival rate. Measurements and Main Results: Trichostatin A significantly suppressed histone deacetylase activity and significantly improved the survival rate of mice (56.3%) after postinfluenza pneumococcal infection when compared with vehicle-treated mice (20.0%), which was associated with a significant decrease in the total cell count of the bronchoalveolar lavage fluid. The interleukin-1β level in the serum and the number of natural killer cells in the lungs were significantly lower in the trichostatin A-treated group. Conclusions: The histone deacetylase inhibitor trichostatin A protects mice against postinfluenza pneumonia possibly through multiple factors, including decreasing local cell recruitment into the lungs and suppressing systemic inflammation. Abstract : Supplemental Digital Content is available in the text.